Understanding the drivers of female imprisonment in Scotland - McIvor, Gill (Report, 2011)
Female imprisonment has increased significantly in recent years in Scotland and internationally. This report considers possible explanations for this increasing trend. The authors investigated whether the growth in female imprisonment is attributed to more women getting involved in crime, more serious crimes being committed by women or changes in prosecution and sentencing patterns. The analyses presented here focus on women only, and no comparisons with trends for male offenders were made.